2014
DOI: 10.1093/ijnp/pyu074
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Variations in Stress Coping Behavior Are Mediated by a 5-HT/GABA Interaction within the Prefrontal Corticolimbic System

Abstract: Background:Serotonin and γ–aminobutyric acid (GABA) transmission is crucial in coping strategies.Methods:Here, using mice from 2 inbred strains widely exploited in behavioral neurochemistry, we investigated whether serotonin transmission in medial prefrontal cortex and GABA in basolateral amygdala determine strain-dependent liability to stress response and differences in coping.Results:C57BL/6J mice displayed greater immobility in the forced swimming test, higher serotonin outflow in medial prefrontal cortex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 81 publications
2
26
0
Order By: Relevance
“…With regard to individual coping styles to stress, GABArgic transmission in the BLA has been shown to function in the response of C57BL/6 and DBA/2 mice in the forced swimming test. C57BL/6 mice exhibit the highest levels of passive-coping behavior [58,59,[66][67][68]. We have found that C57BL/6 mice show greater immobility in the forced swimming test (an index of passive-coping behavior), likely due to greater GABA outflow in the BLA, compared with DBA/2 mice [59].…”
Section: Gabamentioning
confidence: 72%
See 3 more Smart Citations
“…With regard to individual coping styles to stress, GABArgic transmission in the BLA has been shown to function in the response of C57BL/6 and DBA/2 mice in the forced swimming test. C57BL/6 mice exhibit the highest levels of passive-coping behavior [58,59,[66][67][68]. We have found that C57BL/6 mice show greater immobility in the forced swimming test (an index of passive-coping behavior), likely due to greater GABA outflow in the BLA, compared with DBA/2 mice [59].…”
Section: Gabamentioning
confidence: 72%
“…Wellman and colleagues showed that the loss of 5-HTT function in mice compromises their ability to cope with environmental stress and effects morphological abnormalities in the BLA and mpFC-changes that were related to amygdalar hyperactivity and hypofunction in the pFC [132]. Further, regarding the function of the prefrontal 5-HT system in modulating the amygdalar stress response, we have demonstrated that bilateral selective 5-HT depletion in the mpFC in mice decreases the BLA GABA release that is induced by restraint stress and passive coping in the forced swimming test, implicating 5-HT and GABA transmission-mediated pFC/amygdala connectivity as a critical neural mechanism of stress-induced behavior [58,59].…”
Section: Neuronal Circuits In the Stress Responsementioning
confidence: 76%
See 2 more Smart Citations
“…Consistent with this viewpoint, impaired corticolimbic modulation has been suggested to be an important mechanism of stress-induced (p.199) hyperalgesia (Wang et al, 2013). Interestingly, this corticolimbic system was found to be related to strain differences in stress-coping behavior in mice (Andolina et al, 2014). Hence, reward/motivational circuits can be targeted by employing real-time feedback of neural activity, by fMRI (Chapin et al, 2012) or brain stimulation using TMS or deep brain stimulation; and these procedures hold promise for advancing future pain management (Navratilova & Porreca, 2014).…”
Section: Pharmacotherapeutic Approachesmentioning
confidence: 78%